2011
DOI: 10.1118/1.3637495
|View full text |Cite
|
Sign up to set email alerts
|

RF tissue-heating near metallic implants during magnetic resonance examinations: An approach in the ac limit

Abstract: The presented ac approach to RF heating near an implant, which mimics specific values for R, L, and C, allows for closed formulas to estimate the potential of RF energy transfer. A first reference point for worst-case determination in MR testing procedures can be obtained. Numerical approaches, necessary to determine spatially resolved heating maps, can be supported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The associated electric field component at position r is given by E(boldr)=iω2r×(×A(r)). The vector potential and the electric field in the cylinder are described by a solution of the full Maxwell's equations, as the spatial dimensions of the object can be in the range of the RF wavelength at 3T field strength. In contrast, the impact of the metal rod is described in the near‐field approach by an electrical equivalent circuit comprising the rod's inductance L and resistance R , as well as the conductance G and capacitance C of the surrounding medium. The electric field induces an electric current in the rod at position p Iz(boldp)=lnormalRiωL+R+(G+iωC)1Ez(boldp), also depending on the Larmor frequency ω, corresponding to the static magnetic field.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The associated electric field component at position r is given by E(boldr)=iω2r×(×A(r)). The vector potential and the electric field in the cylinder are described by a solution of the full Maxwell's equations, as the spatial dimensions of the object can be in the range of the RF wavelength at 3T field strength. In contrast, the impact of the metal rod is described in the near‐field approach by an electrical equivalent circuit comprising the rod's inductance L and resistance R , as well as the conductance G and capacitance C of the surrounding medium. The electric field induces an electric current in the rod at position p Iz(boldp)=lnormalRiωL+R+(G+iωC)1Ez(boldp), also depending on the Larmor frequency ω, corresponding to the static magnetic field.…”
Section: Methodsmentioning
confidence: 99%
“…Resonance effects are not the primary focus of this work and are avoided in the following investigations. Similar to previous publications , the length of the metal rod, i.e., the antenna, is compared with the RF wavelength in the medium to estimate the impact of the resonance effect. According to the Biot‐Savart law for a conductor of infinite length, the current gives rise to a magnetic field, which superimposes the original one.…”
Section: Methodsmentioning
confidence: 99%
“…A seamless implant system can be fabricated that encapsulates the device with the same LCP substrate that comprises the electrode carrier. Another advantage of LCP as a packaging material is its RF compatibility, which is desirable as conventional metallic packages cause RF heating and image distortion during conventional MR imaging . It was reported that the metal‐based device generated the significant amount of artifacts in the proximity of the package in the 3.0 T images while the MR images near the LCP‐based device clearly showed the brain structures .…”
Section: Discussionmentioning
confidence: 99%
“…Although a less likely scenario, there is also the potential that a loop‐containing implanted device might act as a circuit in resonance, in which case a very significant amount of energy may be transferred, possibly resulting in destruction of the device and damage to surrounding tissue. An unblanked receive coil would be an example …”
Section: The Rf Fieldmentioning
confidence: 99%